The Effect of Service Quality to Customer Satisfaction by Using Internet Banking Service in Jambi - Assegaff, Setiawan (School of Business and Management Institut Teknologi Bandung, 2016)
Abstract. Internet banking service has become an important part of the current banking products. It could be said almost all bank, which is operating in Indonesia, have to equip their products by providing internet-banking services for its customers. Despite the fact that the investment to build the internet banking service has been carried out by almost all banks in Indonesia, but in fact the use of internet banking adoption is still not significant. Banking in Indonesia still filled with questions about Internet banking services such as what exactly is a yearning of each customer. Because it is highly important for banking in Indonesia to fully understand the quality of the services, which they had provided. A good understanding of the customer's perception when using internet banking services will certainly be a strong foundation for bank in Indonesia to be able in provide an appropriate internet services, effective and efficient for customers. If the customer hope has been fulfilled, that customers will be satisfied and will ultimately loyal to the internet banking service. This study examines the elements that will affect the quality of the internet banking service for customers. A survey conducted by inviting 115 respondents. Data were analyzed using SEM method utilizing Smart PLS software. This study found that the